2016
DOI: 10.1515/aot-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Metrology for the production process of aspheric lenses

Abstract: Metrology revealing the form deviation of an aspheric surface is a fundamental part of all different production processes of aspheric lenses. Different processing steps have different requirements for the production. A selection of measuring instruments commonly applied in these processes is presented. This contains tactile and optical pointwise measuring instruments and laser interferometer systems. The principle functionality and the properties are presented. An overview of the application of these systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In this situation, comparisons are a key factor in gaining new insights. Comparisons [6][7][8][9] have shown that, while some progress has been achieved, further improvements are also necessary. Most of the specimens used in these comparison studies were conventional spherical or aspherical surfaces made of glass.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, comparisons are a key factor in gaining new insights. Comparisons [6][7][8][9] have shown that, while some progress has been achieved, further improvements are also necessary. Most of the specimens used in these comparison studies were conventional spherical or aspherical surfaces made of glass.…”
Section: Introductionmentioning
confidence: 99%
“…CMMs have the advantage of providing absolute form information, but this process is slow and gives only pointwise information [17], even though the point density in the scanning direction can be very high. The tactile devices used in the study were the Isara 400 [18]; MarSurf LD260 Aspheric 3D [19]; UA3P 3D Profilometer [20]; and Taylor Hobson PGI [21].…”
Section: Measurement Methods and Devicesmentioning
confidence: 99%
“…On the other hand, the measurement procedure is contact-less, thereby sparing the surface from potential scratches or digs. The optical point sensors used were MarForm MFU200 Aspheric 3D [19,22] and LuphoScan [23,24].…”
Section: Measurement Methods and Devicesmentioning
confidence: 99%
“…RMS deviations were found to be of the order of tens of nanometres, up to 90 nm in the case of the strong asphere. There have been several advances in optical technologies for asphere measurement (see e.g., [13], [129]) and contact CMSs can be employed (e.g., see [26], [288]). Traceability for these instruments is now in place, thanks to developments in the EMPIR project FreeFORM (see [9] for a summary of the project outputs).…”
Section: Spherical and Aspherical Form Measurement Artefactsmentioning
confidence: 99%